2020
DOI: 10.1155/2020/1318480
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Risk of the Hospital Environment in the Center of Morocco: A Case of Care Unit Surfaces

Abstract: Background. Equipment and hospital surfaces constitute a microbial reservoir that can contaminate hospital users and thus create an infectious risk. The aim of this work, which was carried out for the first time at a hospital in Meknes (regional hospital in the center of Morocco), is to evaluate the microbiological quality of surfaces and equipment in three potential risk areas (burn unit, operating room, and sterilization service). Methods. This study was carried out over a period of 4 months (February–May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The majority of bacteria isolated from the different studied services' surfaces are Gram-positive germs. This result is similar to those reported in a study carried out in a hospital center in Fez and contradicts other studies [ 4 , 13 , 25 ]. This contradiction could be due to the hospital size (especially its bed capacity) and the studied department specificity, as our study was carried out more precisely in the surgery departments of a small hospital center, while the other studies were carried out in other departments.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of bacteria isolated from the different studied services' surfaces are Gram-positive germs. This result is similar to those reported in a study carried out in a hospital center in Fez and contradicts other studies [ 4 , 13 , 25 ]. This contradiction could be due to the hospital size (especially its bed capacity) and the studied department specificity, as our study was carried out more precisely in the surgery departments of a small hospital center, while the other studies were carried out in other departments.…”
Section: Discussionsupporting
confidence: 89%
“…In the same contexts, other Moroccan studies have reported contamination of three departments, namely, the burns unit, the sterilization department, and the operating room, with varying rate prevalence of contamination (70%, 13%, and 7%, respectively). The same study showed that the autoclave, the bed rails, the bedside tables, and the operating tables are the most contaminated sites [ 8 ]. Some areas or equipment are more contaminated than others, while relevant research has shown a high prevalence of contamination of high contact surfaces and equipment around the patient's bed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%